COMMENTS ABOUT DECORATIONS OF OLD TERMIZ MERCURY JUGS - Temirova Munira (American Journals Publishing, 2023)
This article focuses on Old Termiz potters and their pottery products in the Middle Ages. Information about the most interesting product of this period, mercury jugs and their external decoration (ornaments) and their description is given.
Keywords: Pottery area, Old Termiz, ornament, ring, plant leaves, conical vessels, prints and others.